Effect of Posteroanterior Lumber Spine Mobilization Versus McKenzie Prone Push Ups on Pain and Functional Disability in Subjects with Non-Specific Low Back Pain: Posteroanterior Lumber Spine Mobilization Versus McKenzie - Ali , Saman; Ahmed Zahoor , Idrees; Ghaffar, Noman; Ali Rana , Arif; Ahmad, Irfan; Idrees , Qasim (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2023)
85% of the population has non-specific back pain. Posteroanterior (PA) lumbar mobilization and Push-up exercises are primarily used in physical therapy for back pain. Objective: To know the outcomes of posteroanterior spinal mobilization and prone push-ups on nonspecific lower back pain. Methods: The randomized clinical trial was done with 30 subjects meeting inclusion criteria and were randomly selected by non-probability/purposive sampling technique from the Department of Physical Therapy, Mayo Hospital Lahore. The 4 weeks study was conducted in which 2 groups with 15 in each group were formed. Group I was treated with PA lumbar glide while group II was treated with prone Push-ups. VAS and functional disability index were used to evaluate pre-treatment and post-treatment. Results: A significant decrease in mean pain score was noted in both groups. Results did not show any statistically significant differences between groups for any parameter. The study has given evidence that supports the use of posteroanterior mobilization and prone push-ups to reduce pain, improve range of movement, and disability reduction in patients with nonspecific low back pain. It also showed that posteroanterior mobilization was more beneficial than prone Push-ups. Conclusion: Both PA mobilization and Push-ups can be used as effective maneuvers for the treant of non-specific low back pain